Ppn2 Polyphosphatase Improves the Ability of S. cerevisiae to Grow in Mild Alkaline Medium - Irina A. Eliseeva; Lubov Ryazanova; Larisa Ledova; Anton Zvonarev; Airat Valiakhmetov; Maria Suntsova; Aleksander Modestov; Anton Buzdin; Dmitry N. Lyabin; Ivan V. Kulakovskiy; Tatiana Kulakovskaya (Journal of Fungi)
Inorganic polyphosphates and respective metabolic pathways and enzymes are important factors for yeast active growth in unfavorable conditions. However, particular proteins of polyphosphate metabolism remain poorly explored in this context. Here we report biochemical and transcriptomic characterization of the CRN/PPN2 yeast strain (derived from Ppn1-lacking CRN strain) overexpressing poorly studied Ppn2 polyphosphatase. We showed that Ppn2 overexpression significantly reduced lag phase in the alkaline medium presumably due to the ability of Ppn2 to efficiently hydrolyze inorganic polyphosphates and thus neutralize hydroxide ions in the cell. With RNA-Seq, we compared the molecular phenotypes of CRN/PPN2 and its parent CRN strain grown in YPD or alkaline medium and detected transcriptomic changes induced by Ppn2 overexpression and reflecting the adaptation to alkaline conditions. The core set of upregulated genes included several genes with a previously unknown function. Respective knockout strains (∆ecm8, ∆yol160w, ∆cpp3, ∆ycr099c) exhibited defects of growth or cell morphology in the alkaline medium, proving the functional involvement of the respective proteins in sustaining growth in alkaline conditions.